1276. Noninvasive Assessment of Change in Hepatic Fibrosis Following Initiation of Integrase Inhibitors in Women Living with HIV. (15th December 2022) - Yu, Michael A; Gerig, Logan; Mehta, Cyra Christina; Yusef, Oyindamola; Musonge-Effoe, Joffi; Alvarez, Jessica; Spence, Amanda B; Albrecht, Svenja; Alcaide, Maria L L; Adimora, Adaora A; Abraham, Alison G; French, Audrey L; et al.
Abstract: Background: Nonalcoholic fatty liver disease (NAFLD) is highly prevalent in persons with HIV and can lead to hepatic fibrosis. Integrase strand-transfer inhibitors (INSTIs), first-line agents in antiretroviral therapy (ART), are associated with increased body mass index (BMI), particularly in women living with HIV (WLWH). We evaluated change in hepatic fibrosis risk following INSTI initiation in WLWH. Table 1. Change over time in hepatic fibrosis scores among group switching to INSTI-regimens versus group staying on non-INSTI regimens INSTI=integrase strand-transfer inhibitor; SD=standard deviation; FIB-4=Fibrosis-4 Score (calculated by Age*AST/[platelet count*ALT1/2]; APRI=AST to Platelet Ratio Index (calculated by [AST/AST upper limit of normal]/platelet count); NFS = Non Alcoholic Fatty Liver Disease Fibrosis Score (calculated by -1.675+(0.037*age) + (0.094*body mass index)+(1.13*hyperglycemia or diabetes [yes=1, no=0])+ (0.99*AST/ALT)-(0.013*platelet count)-(0.66*albumin)); CI=Confidence Interval. Linear regression model with unstructured covariance matrix for repeated observations with a person. Adjusted models for all outcomes included the following covariates: age, race/ethnicity, education, baseline CD4 lymphocyte count, baseline antiretroviral anchor drug, and abacavir, tenofovir disoproxil fumarate, and tenofovir alafenamide use. Body mass index was included in models for FIB-4 and APRI only. Age was included for APRI only. Methods: Data from 2007-2020 were analyzed from virologically-suppressed WLWH enrolled in the Women's Interagency HIV Study (WIHS). We excluded WLWH with untreated viral hepatitis, heavy alcohol use and autoimmune or metabolic chronic liver disease. WLWH who switched to or added an INSTI to ART were compared to women who remained on non-INSTI ART. Outcomes included change in noninvasive markers of hepatic fibrosis: Fibrosis-4 (FIB4), AST to Platelet Ratio Index (APRI), and NAFLD fibrosis score (NFS), measured 4-12 months before and 4-19 months post INSTI switch/add. Longitudinal linear regression models compared change over time in each outcome by group, adjusted for covariates. Results: 872 WIHS participants (323 INSTI, 549 non-INSTI) were followed for a median 3.0 years (Q1 2.0, Q3 4.5). Mean age was 47.2 years (SD 9.0), 61% were Non-Hispanic Black, and mean BMI was 31.4 (8.8) kg/m 2 . Absolute mean changes in FIB4, APRI, and NFS scores were +0.021, -0.005, +0.194, respectively, in the INSTI group compared to +0.003, -0.011, +0.016, respectively, in the non-INSTI group (Table 1). No significant differences in mean AST and ALT change between the INSTI and non-INSTI groups were noted. There was a significant increase in NFS score in the INSTI group (p< 0.0001) and this difference remained in adjusted models (p=0.0135). Compared to the non-INSTI group, a larger proportion of participants in the INSTI group changed to a higher NFS risk category: 15.7% vs 9.0%, p=0.014. Conclusion: Starting INSTIs was associated with minimal change in FIB4 and APRI scores but increased NFS score in WLWH. The increase in NFS score likely reflects BMI gain with INSTI use, as BMI is not factored into FIB4 or APRI calculators and AST and ALT did not change significantly. Nonetheless, patients starting INSTIs need close monitoring of metabolic changes and low thresholds for additional noninvasive liver fibrosis testing. Disclosures: Michael A. Yu, MD, Ligera: Advisor/Consultant Maria L L. Alcaide, MD, Gilead: Advisor/Consultant Adaora A. Adimora, MD, MPH, Gilead: Advisor/Consultant|Gilead: Grant/Research Support|Merck: Advisor/Consultant|Merck: Grant/Research Support Jennifer C. Price, MD, PhD, Abbvie: Grant/Research Support|Gilead: Grant/Research Support|Merck: Grant/Research Support Phyllis C. Tien, MD, MSc, Gilead: Grant/Research Support|Merck: Grant/Research Support Cecile D. Lahiri, MD, MS, Theratechnologies: Advisor/Consultant.